2020
DOI: 10.3390/diagnostics10090645
|View full text |Cite
|
Sign up to set email alerts
|

Artifacts in Musculoskeletal Ultrasonography: From Physics to Clinics

Abstract: Ultrasound appears to be the most useful imaging tool in the diagnosis and guided treatment of musculoskeletal disorders. However, ultrasonography has been criticized for being user dependent. Therefore, medical professionals should be familiar with the basic principles of ultrasound imaging (e.g., physics and technical skills) to diminish artifacts and avoid misinterpretation. In this review, we focused on the physics of common artifacts, their clinical significance, and the ways to tackle them in daily pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 33 publications
(36 reference statements)
0
40
0
Order By: Relevance
“…The ER TM is a common ultrasound parameter to evaluate tendon quality ( 18 , 25 ). While isolating a deeper structure, the target appears more hypoechoic due to absorption of ultrasound energy ( 36 ). Using echogenicity of the overlying muscles as the reference, the ER TM can partly counteract the influences of signal gain at various depths, which is considered better than using tendon echogenicity alone for comparisons among different subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The ER TM is a common ultrasound parameter to evaluate tendon quality ( 18 , 25 ). While isolating a deeper structure, the target appears more hypoechoic due to absorption of ultrasound energy ( 36 ). Using echogenicity of the overlying muscles as the reference, the ER TM can partly counteract the influences of signal gain at various depths, which is considered better than using tendon echogenicity alone for comparisons among different subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A-lines are repetitive horizontal artifacts derived by repetitive reflection from the tissue-gas interface to the transducer (Figure 4C )[ 48 ]. B-lines are well defined, vertical, laser-like artifacts, and are generated by a ring down effect when the sound waves pass through gas bubbles associated with fluid collection, and provokes resonance within the air-fluid interface, emitting continuous waves back to the transducer (Figure 4D )[ 49 ]. A comet-tail artifact is produced when ultrasound beams are repeatedly reflecting on the shallow and deep sides of gas bubbles (Figure 4E )[ 50 ], which usually looks like an inverted triangular hyperechoic lesion with reduced thickness and strength (Figure 1A ).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have indicated that clean shadowing and dirty shadowing in essence correlate with the properties of the surface of the subjects, curvature and roughness, rather than the inner nature[ 57 ]. Dirty shadowing is considered the hallmark of ultrasound in EPN, and it is generated by reflection of ultrasound waves in multiple directions into the gas bubbles[ 49 ] (Figure 4F ). We suggest that knowledge of the sonographic features of air-related artifacts in EPN plays an important role in physicians making an early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anistropy occurs when tissues show abnormal echogenicity, most commonly loss of echogenicity, due to an oblique insonating angle [ 91 ]. Tendons or ligaments may appear as hypoechoic and thus could be misinterpreted as tendinosis or tears [ 92 ]. Edge artifact occurs when a curved surface reflects the US beam away from the transducer, appearing as hypoechoic parallel lines projecting along the edges of the target [ 92 ].…”
Section: Imaging Modalities For the Hindfoot And Posterior Anklementioning
confidence: 99%
“…Tendons or ligaments may appear as hypoechoic and thus could be misinterpreted as tendinosis or tears [ 92 ]. Edge artifact occurs when a curved surface reflects the US beam away from the transducer, appearing as hypoechoic parallel lines projecting along the edges of the target [ 92 ]. Edge artifact could lead to the curved Achilles tendon being misinterpreted as paratenon thickening [ 92 ].…”
Section: Imaging Modalities For the Hindfoot And Posterior Anklementioning
confidence: 99%